Improving Short Story Writing Skills Through Cooperative Learning Using the Educational Video "7 Habits of Great Indonesian Children" for Ninth Grade Students at Budhi Mulia Integrated Junior High School - Riksa Fathan Firdaus; Iis Ristiani (West Science Social and Humanities Studies, 2025)
The ability to write short stories is one of the important competencies in learning Indonesian, but in reality, many students still experience difficulties in developing intrinsic elements of short stories such as plot, characters, conflict, and effective use of language. Based on the results of initial observations in grade IX of Budhi Mulia Integrated Junior High School, it was found that students' short story writing skills were in the poor category, with an average score of 59.8, and only 28% of students achieved the Minimum Completion Criteria (KKM). This condition indicates the need for learning strategies that can significantly improve students' creativity, motivation, and writing skills. Therefore, this study aims to improve short story writing skills through the application of the Cooperative Learning method assisted by the educational video "7 Habits of Great Indonesian Children." This study used the Classroom Action Research (CAR) method with the Kemmis and McTaggart model which was implemented in two cycles. The research instruments included short story writing tests, student and teacher activity observation sheets, interview guidelines, and documentation. Data were analyzed using quantitative analysis techniques in the form of calculating the average test results and the percentage of learning completion. The results showed a significant increase in short story writing skills. The average student score increased from 59.8 (pretest) to 72.4 in cycle I, and increased again to 80.2 in cycle II. The percentage of learning completion also increased from 28% to 76%, and finally reached 92% in cycle II. Educational videos were proven to help students understand character values and explore ideas, while the Cooperative Learning model increased group interaction, discussion, and creativity. Based on these findings, it can be concluded that the Cooperative Learning method assisted by educational videos is effective in improving the short story writing skills of grade IX students.